2017
DOI: 10.1080/08998280.2017.11930210
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acute Care Health Care Providers in Cardiopulmonary Resuscitation Compressions in Normal and Obese Adult Simulation Manikins

Abstract: Annually, over 350,000 persons require cardiopulmonary resuscitation (CPR), either in or outside of the hospital. With obesity a rising health issue in the United States, concerns exist regarding the efficacy of quality compressions for CPR in obese patients. The aims of this study were to determine if the compressions for three adult simulation manikins (normal, obese, and morbidly obese) met quality guidelines; to examine any differences in quality of chest compressions performed by health care providers bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This is consistent with the findings of other studies that suggest a positive relationship between rescuer weight and adequacy of compressions 16,20,21,26 . It is also possible that younger participants have a higher proportion of lean muscle, more cardiovascular fitness or a less nihilistic approach; this is purely speculative, however is consistent with work recently published by Tellson et al 16,21 . Advances in technology have allowed the introduction of a number of new techniques into resuscitation practice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with the findings of other studies that suggest a positive relationship between rescuer weight and adequacy of compressions 16,20,21,26 . It is also possible that younger participants have a higher proportion of lean muscle, more cardiovascular fitness or a less nihilistic approach; this is purely speculative, however is consistent with work recently published by Tellson et al 16,21 . Advances in technology have allowed the introduction of a number of new techniques into resuscitation practice.…”
Section: Discussionsupporting
confidence: 92%
“…In the only other example in the literature, Tellson et al randomised 61 (predominantly female) healthcare workers to perform 30 compressions on one of three manikins, two of which had been re-designed to emulate an obese and a morbidly obese patient respectively 16 . They too found that the quality of CPR decreased significantly between a 'normal' and an 'obese' manikin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of mechanical chest compression devices might be considered although body dimensions and slope of the anterior chest wall limit usability of most devices. The upper limits include sternum height of 303 or 340 mm and chest width of 449 or 480 mm for piston devices, chest circumference of 130 cm, chest width of 380 mm, and body weight of 136 kg for devices equipped with a load-distributing band [ 68 , 69 ].…”
Section: Complex Emergency Scenarios In Obese Patientsmentioning
confidence: 99%
“…It is evident that patients with obesity pose unique care challenges to those nurses who care for them, including pain management [ 24 ] and wound management which can necessitate the need for more complex wound management strategies to promote healing [ 18 ] and the maintenance of skin integrity [ 25 ]. Wound management in patients with obesity is further complicated by a lack of an evidence base, which has been identified as a particular issue [ 26 ] but also in many other aspects of care including patient centred communication [ 27 , 28 ], mobilisation [ 29 ], minimisation of pressure ulcers [ 30 ], cardiopulmonary resuscitation [ 31 ] and respiratory care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%